Modified Generalized Rayleigh Distribution: Model and Properties - Lal Babu Sah Telee; Vijay Kumar (Pravaha, 2022)
This article is based on formulation of a new three parameters continuous distribution. Some important properties are discussed here. Different methods of estimation are used for parameter estimation. Validity of the model is tested using different information criteria as well as some graphical plots. For applicability testing, a real data set is taken. For model comparison we have considered some previously introduced probability models and is found that proposed model fits the real life data better compared to considered models.